The new face of international intervention and conflict management - Shuriye, Abdi Omar (2011)
International interventions and conflict managements are part of the mechanisms performed by the international community through international and regional organizations. This paper argues that although the UN and other governmental organizations made repetitive diplomatic attempts through its resolutions in intervening political calamities and sending peacekeeping forces, the mechanism of these efforts need further scrutiny and simplification. In the last few years alone we have witnessed the Sudanese region of Dafur and Lebanon. On the ongoing conflicts, the AU struggles to concur on schema to maintain African forces in Somalia, and NATO forces on the other side are engaged in fierce battles against Taliban fighters in Afghanistan, all under one name: international intervention. Undoubtedly, international interventions are of diverse nature and are associated with political and ethical hallucination.